International Legal and Administrative-Criminal Regulation of Service Relations - Leheza, Yevhen; Yerko, Iryna; Kolomiichuk, Viacheslav; Lisniak, Mariia (Jurnal Cita Hukum, 2022)
The purpose of the research the research is devoted to the coverage of international legal acts andstandards in European and international practice for the provision of public services as a direction of reforming legal education in Ukraine.  Methodology. Review of materials and methods is performed on the basis of analyzing documentary materials on regulation of the service legal relations. Conclusions. The directions of improving domestic legislation on the provision of public services taking into account international legal standards are proposed: the development of the theory of public services, which consists in consolidating conceptual and categorical provisions in the Concept of public services, principles of public services, quality criteria for the provision of public services, and the like; unification of the legal regulation of administrative procedures by adopting the Administrative Procedure Code of Ukraine, which would clearly disclose the issue of providing public services; fixing in the legal acts the types of legal guarantees to ensure the legality of the provision of public services: monitoring the activities of public administration entities on the provision of public services; holding public servants accountable for refusing to provide a certain type of public service; bringing into line with European experience the requirements for adoption, amendment, cancellation and the possibility of appealing individual administrative acts that are the results of the provision of public services; decentralization of power, which consists in justifying an increase in the powers of local authorities in comparison with public authorities.Keywords: Accessibility; Rights; Transparency; Service; Service RelationsPeraturan Hukum Internasional dan Administratif-Pidana Hubungan LayananAbstrakTujuan penelitian penelitian ini dikhususkan untuk cakupan tindakan hukum internasional dan standar dalam praktek Eropa dan internasional untuk penyediaan layanan publik sebagai arah reformasi pendidikan hukum di Ukraina. Metodologi. Kajian bahan dan metode dilakukan atas dasar analisis bahan dokumenter tentang pengaturan hubungan hukum pelayanan. Kesimpulan. Arahan perbaikan legislasi domestik tentang penyediaan layanan publik dengan mempertimbangkan standar hukum internasional diusulkan: pengembangan teori layanan publik, yang terdiri dari konsolidasi ketentuan konseptual dan kategoris dalam Konsep layanan publik, prinsip-prinsip layanan publik, kriteria mutu penyelenggaraan pelayanan publik, dan sejenisnya; penyatuan peraturan hukum prosedur administrasi dengan mengadopsi Kode Prosedur Administratif Ukraina, yang dengan jelas akan mengungkapkan masalah penyediaan layanan publik; penetapan dalam perbuatan hukum jenis-jenis jaminan hukum untuk menjamin legalitas penyelenggaraan pelayanan publik: pemantauan kegiatan badan administrasi publik dalam penyediaan pelayanan publik; meminta pertanggungjawaban pegawai negeri karena menolak memberikan jenis layanan publik tertentu; membawa sejalan dengan pengalaman Eropa persyaratan untuk adopsi, amandemen, pembatalan dan kemungkinan banding tindakan administratif individu yang merupakan hasil dari penyediaan layanan publik; desentralisasi kekuasaan, yang terdiri dari pembenaran peningkatan kekuasaan otoritas lokal dibandingkan dengan otoritas publik.Kata kunci: Aksesibilitas; Hak; Transparansi; Layanan; Hubungan Layanan Международно-Правовое И Административно-Уголовное Регулирование Сервисных Правоотношений Аннотация. Цель исследования исследование посвящено освещению международно-правовых актов и стандартов в европейской и международной практике сервисных правоотношений как направления реформирования юридического образования в Украине. Методология. Обзор материалов и методик выполнен на основе анализа документальных материалов по регулированию сервисных правоотношений. Выводы. Предложены направления совершенствования отечественного законодательства сервисных правоотношений с учетом международно-правовых норм: развитие теории государственных услуг, заключающееся в закреплении понятийно-категориальных положений в Концепции государственных услуг, принципов оказания государственных услуг, критерии качества оказания государственных услуг и тому подобное; унификация правового регулирования административных процедур путем принятия Административно-процессуального кодекса Украины, который четко раскрывал бы вопрос предоставления государственных услуг; закрепление в правовых актах видов правовых гарантий обеспечения законности предоставления государственных услуг: контроль за деятельностью субъектов государственного управления по оказанию государственных услуг; привлечение государственных служащих к ответственности за отказ в предоставлении определенного вида государственной услуги; приведение в соответствие с европейским опытом требований о принятии, изменении, отмене и возможности обжалования отдельных административных актов, являющихся результатами оказания государственных услуг; децентрализация власти, заключающаяся в обосновании увеличения полномочий органов местного самоуправления по сравнению с органами государственной власти.Ключевые слова: доступность; права; прозрачность; служба; сервисные правоотношения